Public innovation of waste management completion strategy for community welfare in Lebak district - Permana, Deni; Febrianto, Ega; Saepudin, Eli Apud (Trigin Publisher, 2024)
An innovative solution to the waste problem in Lebak Regency, Banten, Indonesia. This innovation aims to improve public health, preserve the environment, and boost the local economy through integrated and sustainable waste management. This innovation has shown positive results in improving public health, preserving the environment, and boosting the local economy. Communities in Lebak Regency are becoming more aware of the importance of good waste management, and more people are involved in waste processing and recycling activities. The research method used was descriptive qualitative. The results of this research have had an impact on reducing the number of waste-related diseases, improving environmental quality, and creating new jobs in the waste management sector. The Public Innovation of Waste Management Completion Strategy for Community Welfare in Lebak Regency can be an example for other regions in Indonesia in overcoming waste problems and improving community welfare.